Comparative study of zakah and modern taxation - Abu Bakar, Nur Barizah; Abdul Rahman , Abdul Rahim (King Abdulaziz University, 2007)
This paper critically discusses the concept of zakah and taxation. The main objective of the paper is, first, to compare and contrast zakah and taxation, especially on the legal, economic, social, ethical and spiritual aspects. Secondly, the paper aims to examine issues related to the implementation of zakah in modern time by reviewing the practices of zakah and taxation in the early Islamic period and exploring the issues in the context of Malaysia. The paper indicates that zakah greatly differs from the taxation system. Zakah aims not only to achieve religious merit but also to become part of the modern state fiscal policies and share a greater role in removing inequalities in the society. The paper argues that there may be lack of proper implementation of zakah in Muslim countries which limits the success of the noble aims of zakah. Finally, the paper indicates the urgent need for education and political will of modern governments to ensure the success and survival of zakah.